Frühchristliche Denkmäler mit Psalmzitaten - Pillinger, Renate (Mitteilungen zur christlichen Archäologie, 2023)
Quotations from the Psalms appear on practically all types of monuments, and especially in tombs. Commonly featured in the liturgy, including the baptismal liturgy, they mostly appear in Greek. On bracelets and amulets, as well as above entrances and on sarcophagi, they have an apotropaic function. Often the message of the Psalm is related typologically to Christ. Accordingly, Psalm quotations are also found in churches, mainly on floors in the altar area as a juxtaposition of burnt and Eucharistic sacrifices, but rarely are they found on textiles. One particularly interesting example, a fragment probably from the robe of a deacon, is housed in the MAK in Vienna.